Alumni series: roles of community pharmacists in fall prevention / Mohd Shah Rezan Hamzah - Hamzah, Mohd Shah Rezan (Faculty of Pharmacy, 2023)
Falls can result in injuries that often result in hospitalization and mortality. Fall-related injuries can cause long-term impacts on health outcomes and overall quality of life. Addressing health issues stemming from falls can be an expensive endeavor, constituting around 0.85% to 1.5% of a country's total healthcare spending [1].